Bibliometric Analysis of Chimeric Antigen Receptor-Based Immunotherapy in Cancers From 2001 to 2021 - Ou, Zhanpeng; Qiu, Ling; Rong, Haixu; Li, Bowen; Ren, Siqi; Kuang, Shijia; Lan, Tianjun; Lin, Hsinyu; Li, Qunxing; Wu, Fan; Cai, Tingting; Yan, Lingjian; et al. (Frontiers in Immunology, 2022)
Background: Chimeric antigen receptor (CAR)-based immunotherapy has shown great potential for the treatment of both hematopoietic malignancies and solid tumors. Nevertheless, multiple obstacles still block the development of CAR-based immunotherapy in the clinical setting. In this study, we aimed to summarize the research landscape and highlight the front lines and trends of this field. Methods: Literature published from 2001 to 2021 was searched in the Web of Science Core Collection database. Full records and cited references of all the documents were extracted and screened. Bibliometric analysis and visualization were conducted using CiteSpace, Microsoft Excel 2019, VOSviewer and R software. Results: A total of 5981 articles and reviews were included. The publication and citation results exhibited increasing trends in the last 20 years. Frontiers in Immunology and Blood were the most productive and most co-cited journals, respectively. The United States was the country with the most productive organizations and publications in the comprehensive worldwide cooperation network, followed by China and Germany. Carl H June published the most papers with the most citations, while Maude Shannon L ranked first among the co-cited authors. The hotspots in CAR-based therapy research were multiple myeloma, safety and toxicity, solid tumors, CAR-engineered immune cells beyond T cells, and gene editing. Conclusion: CAR-based immunotherapy is a promising treatment for cancer patients, and there is an emerging movement toward using advanced gene modification technologies to overcome therapeutic challenges, especially in solid tumors, and to generate safer and more effective universal CAR-engineered cell products.